Rural High School Students’ Attitude toward Literature in English; A Descriptive Study at SMA N 1 Batipuh - Devina Damuri; Delvi Wahyuni (Universitas Negeri Padang, 2021)
The new regulation in curriculum 2013 required senior high schools students to choose a compulsory subject that is generally known as elective course. One of all compulsory subjects in elective course is English elective class. Elective course are also implemented in every senior high schools in Indonesia including rural senior high schools. There are some obstacles to learning English in rural areas. Hence, the researcher is interested to research rural Senior High School students' attitudes toward literature in English. This study was descriptive qualitative research. The participants of this research were 22-second grade students as representative of Social Science class in second grade in SMA N 1 Batipuh. The instrumentations of this research are collected from questionnaire and interview. As for the points to the students, namely the favorite genre of literature, benefits of learning literature, topic preferences, the use of language in the classroom, and also the learning obstacles in rural senior high schools. The findings of this research showed that rural students have a positive attitude towards literature in English.